The international law of the sea - Tanaka, Yoshifumi (Cambridge : Cambridge University Press, 2012)
'The law of the sea is a complex and fascinating subject. This textbook explores the subject from the perspective of public international law, covering all the key topics from the legal regimes governing the different jurisdictional zones, to international co-operation for protection of the marine environment. Students interested in international environmental and natural resources law will find chapters on emerging issues such as the conservation and the protection of natural resources and biodiversity in the oceans. It includes student-friendly features such as chapter overviews, conclusions, figures and tables and further reading sections. Clarity of expression, engaging analysis and comprehensive coverage make this book essential reading for all students of the law of the sea'--
Machine generated contents note: Part I. The Divided Oceans: International Law Governing Jurisdictional Zones: 1. Law of the sea in perspective; 2. Baselines and related issues; 3. Marine spaces under national jurisdiction I: territorial sovereignty; 4. Marine spaces under national jurisdiction II: the sovereign rights; 5. Marine spaces beyond national jurisdiction; 6. Maritime delimitation; Part II. Our Common Ocean: Protection of Community Interests at Sea: 7. Conservation of marine living resources; 8. Protection of the marine environment; 9. Conservation of marine biological diversity; 10. Marine scientific research; 11. Maintenance of international peace and security at sea; 12. Land-locked and geographically disadvantaged states; 13. Peaceful settlement of international disputes.
Includes bibliographical references and index.
Keywords: Law of the sea